2012
DOI: 10.1016/j.ijgo.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence, abortion, and unintended pregnancy: Results from the WHO Multi‐country Study on Women's Health and Domestic Violence

Abstract: IPV is a consistent and strong risk factor for unintended pregnancy and abortion across a variety of settings. Unintended pregnancy terminated through unsafe abortion can result in death or serious complications. Therefore, reducing IPV can significantly reduce risks to maternal and reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
275
2
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(305 citation statements)
references
References 23 publications
17
275
2
11
Order By: Relevance
“…This rate is more consistent with that found in the general population (64%) according to the SIFHSS [12]. The rate of IPV in pregnancy from our study is also higher than that found in other Pacific population studies [10,12,13] which similarly to the SIFHSS have only measured physical violence during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This rate is more consistent with that found in the general population (64%) according to the SIFHSS [12]. The rate of IPV in pregnancy from our study is also higher than that found in other Pacific population studies [10,12,13] which similarly to the SIFHSS have only measured physical violence during pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies were done in the Pacific which utilised the WHO multi-country study methodology [12,13]. The SIFHSS showed that 64% of ever partnered women aged 15-49 reported experiencing physical or sexual violence, or both by an intimate partner [12].…”
Section: Discussionmentioning
confidence: 99%
“…This is a reality in women's lives that relates to abusive partners (9) . Studies (22)(23) show that women who experience various forms of IPV before and/or during pregnancy have a greater chance of performing unsafe abortions. This practice poses a risk to the woman's life, and the opportunity to compromise their mental health (2) .…”
Section: Discussionmentioning
confidence: 99%
“…However, some pregnant women said they had experienced sexual violence before pregnancy, with it being necessary to consider that the pregnancy may have been the result of a violent act perpetrated by the partner (23) . It should be noted that there are risks to sexual and reproductive health and denial of sexual and reproductive rights that are subject to women in IPV situations (6,14) , such as the pregnant women of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Not all pregnant women experience the same level of risk for intimate partner aggression. Women who have unwanted or mistimed pregnancies have significantly higher rates of physical intimate partner aggression compared with women who have intended pregnancies (Pallitto et al 2013). The increased risk does not necessarily diminish following birth.…”
Section: Introductionmentioning
confidence: 96%